Xarifiid copepods (Copepoda: Cyclopoidea: Xarifiidae) parasitic in the coral Psammocora digitata Milne Edwards & Haime 1851 from Taiwan. Issue 2 (23rd April 2021) - Cheng, Yu-Rong; Lin, Yu-Chi
Abstract: Four species of xarifiid copepods, including three new species and one new distribution and host record, are discussed based on specimens obtained from a widely distributed scleractinian coral, Psammocora digitata Milne Edwards & Haime, 1851, collected from Taiwan: Xarifia conrepta sp. nov., X. gracilis sp. nov., X. lata sp. nov., and X. diminuta Humes & Ho, 1967 . Xarifia conrepta sp. nov. is distinguished from its congeners by the morphology of the endopods and exopods of legs, the genital segment, maxilliped, and maxillule; X. gracilis sp. nov. is diagnosed by the morphology of the leg endopods and the region dorsal to the fifth legs; and X. lata sp. nov. by its shorter body length, the terminal armature of endopods and exopods, and the morphology of the maxilliped. The specimens of X . diminuta are similar to those in the original description, except for the undeveloped endopods of legs 3 and 4. Including the three new species, five species of xarifiids are now known to use P . digitata as host, raising to 18 the number of species symbiotic copepod recorded from Psammocora .